Efficient inverted-type perovskite solar cells using UV-ozone treated MoOx and WOx as hole transporting layers. (1st December 2016) - Tseng, Zong-Liang; Chen, Lung-Chien; Chiang, Chien-Hung; Chang, Sheng-Hsiung; Chen, Cheng-Chiang; Wu, Chun-Guey
Highlights: MoOx and WOx hole transporting layers were deposited by a thermal evaporator. UV-ozone treatment to improve surface coverage of perovskite layer. The enhancement on photovoltaic efficiency of perovskite solar cells was discussed. Abstract: Inverted-type perovskite solar cells offer the potential of fabrication by low-temperature solution processing as an alternative to conventional-type perovskite solar cells. PEDOT:PSS is commonly used as the hole transport layer (HTL), but its acidic nature may damage the reliability and stability of the photovoltaic device. In this study, we demonstrate the use of MoOx and WOx HTLs as an alternative to PEDOT:PSS for planar CH3 NH3 PbI3 perovskite solar cells. Furthermore, the MoOx and WOx HTLs are treated using a UV-ozone treatment to improve the surface coverage of the perovskite layer. The resultant conversion efficiency (PCE) for the best cells at AM1.5G illumination with a shadow mask was 13.1%.